2013
DOI: 10.1111/brv.12021
|View full text |Cite
|
Sign up to set email alerts
|

Do predators influence the behaviour of bats?

Abstract: Many aspects of animal behaviour are affected by real-time changes in the risk of predation. This conclusion holds for virtually all taxa and ecological systems studied, but does it hold for bats? Bats are poorly represented in the literature on anti-predator behaviour, which may reflect a lack of nocturnal predators specialized on bats. If bats actually experience a world with minimal anti-predator concerns, then they will provide a unique contrast within the realm of vertebrate ecology. Alternatively, such p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
129
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(132 citation statements)
references
References 156 publications
(223 reference statements)
3
129
0
Order By: Relevance
“…The effects of moonlight on bat activity and fatality at turbines are not well understood, but a study in Alberta, Canada, reported higher fatality rates of silver-haired bats (Lasionycteris noctivagans) at wind turbines on nights when the moon was fully illuminated (29). There is no evidence that tree bat activity in the absence of, or distant from, turbines varies with lunar cycles or illumination (30). Acoustic data gathered on the turbines we monitored, which included many calls from bats passing higher in the airspace than our cameras could image, did not show a trend toward proportionally more activity under moonlit conditions (SI Results), further indicating general activity levels are not influenced by moonlight.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of moonlight on bat activity and fatality at turbines are not well understood, but a study in Alberta, Canada, reported higher fatality rates of silver-haired bats (Lasionycteris noctivagans) at wind turbines on nights when the moon was fully illuminated (29). There is no evidence that tree bat activity in the absence of, or distant from, turbines varies with lunar cycles or illumination (30). Acoustic data gathered on the turbines we monitored, which included many calls from bats passing higher in the airspace than our cameras could image, did not show a trend toward proportionally more activity under moonlit conditions (SI Results), further indicating general activity levels are not influenced by moonlight.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations: (+) preferred, (−) avoided and (0) used in proportion to their availability be distinguished and potential bias may occur, depending on the presence of female-dominated nursery roosts or male roosts in compared sites and habitats. Another bias might result from sampling only the first hours after sunset, as some bat species may shift from more shaded/cluttered to more open habitats during night (Lima and O'Keefe 2013). However, if application of the two successive walks of the transect allows to record the activity of species differing in timing of emergence in a comparable way (Warren et al 2000), it is likely that it allows to control for also such temporal habitat shifts, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Williams & Singh 1951). Some tropical non-insectivorous bat species also demonstrate moonlight avoidance (Saldaña-Vázquez & Munguía-Rosas 2013), but temperate-zone insectivorous bats are not known to change activity patterns in any consistent way (Karlsson et al 2002, Lima & O'Keefe 2013. However, insectivorous bats may move among habitats as they exploit the shifting distributions of insects responding to changes in moonlight levels (Hecker & Brigham 1999).…”
Section: Discussionmentioning
confidence: 99%